Stages of the Ongoing Global Financial Crisis: Is There a Wandering Asset Bubble? - Lucjan T. Orlowski (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2008)
This study argues that the severity of the current global financial crisis is strongly influenced by changeable allocations of the global savings. This process is named a "wandering asset bubble". Since its original outbreak induced by the demise of the subprime mortgage market and the mortgagebacked securities in the U.S., this crisis has reverberated across other credit areas, structured financial products and global financial institutions. Four distinctive stages of the crisis are identified: the meltdown of the subprime mortgage market, spillovers into broader credit market, the liquidity crisis epitomized by the fallout of Bear Sterns with some contagion effects on other financial institutions, and the commodity price bubble. Monetary policy responses aimed at stabilizing financial markets are proposed.
urn:nbn:de:gbv:3:2-7362
Keywords: 330; subprime mortgage crisis; credit crisis; market risk; credit risk; default risk; Level 3 assets; Basel II; Finanzmarktkrise; Vermögen; Bubbles; Spillover-Effekt; Ansteckungseffekt; Hypothek; Kreditmarkt; Geldmarkt; Kreditwürdigkeit; Bankenaufsicht; Welt